Peripapillary retinal nerve fibre layer as measured by optical coherence tomography is a prognostic biomarker not only for physical but also for cognitive disability progression in multiple sclerosis. (February 2019) - Bsteh, Gabriel; Hegen, Harald; Teuchner, Barbara; Amprosi, Matthias; Berek, Klaus; Ladstätter, Felix; Wurth, Sebastian; Auer, Michael; Di Pauli, Franziska; Deisenhammer, Florian; Berger, Thomas
Background: Peripapillary retinal nerve fibre layer (pRNFL) thickness is emerging as a marker of axonal degeneration in multiple sclerosis (MS). Objective: We aimed to prospectively assess the predictive value of pRNFL for progression of physical and cognitive disability in relapsing-remitting MS (RRMS). Methods: In this 3-year longitudinal study on 151 RRMS patients, pRNFL was measured by spectral-domain optical coherence tomography (OCT). We used proportional hazard models, correcting for age, sex, disease duration, Expanded Disability Status Scale (EDSS) and Symbol Digit Modalities Test (SDMT) at baseline, to test a pRNFL thickness ≤88 µm at baseline for prediction of EDSS progression and cognitive decline. We also evaluated the decrease in pRNFL thickness from baseline to year 3 in a multivariate linear regression model. Results: pRNFL thickness ≤88 µm was independently associated with a threefold increased risk of EDSS progression ( p < 0.001) and a 2.7-fold increased risk of cognitive decline within the subsequent 3 years ( p < 0.001). Mean pRNFL delta was −5.3 µm (SD, 4.2). It was significantly negatively impacted by EDSS progression, cognitive decline, higher age and disease duration, while positively impacted by disease-modifying therapy (DMT). Conclusion: Cross-sectional and longitudinal monitoring of pRNFL is useful as a biomarker for prediction of physical and cognitive disability progression in patients with RRMS in everyday clinical practice.